Konsep Pendidikan Islam dalam Interaksi Nabi Khidir dan Nabi Musa dalam Surat Al-Kahfi Ayat 60-82 - Sholihan (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
The Al-Qur'an is a source of Islamic thought that provides a lot of educational inspiration that needs to be developed philosophically and scientifically, as a basic framework for building the concept of Islamic education today. Considering that currently the concepts of Islamic education that have existed since the time of the Prophet are no longer used as guidelines for education. According to them, education is only based on a diploma without prioritizing religious values ​​so education today has lost the spirit of at-tarbiyah. So this research needs to be discussed so that researchers can understand in detail and deeply the concept of Islamic education contained in the Alkahfi letter which contains the story of the prophet Moses and the prophet Khaidir. The method in this research is Library Research with a descriptive analysis approach through interpretations and educational books. Then the author tries to find a concept of Islamic education in these two stories. Meanwhile, the results of research regarding the concept of education in the interaction of Prophet Khaidir and Prophet Musa are that the first thing in an educational institution that must be thought about and formulated properly is the educational objective because, without a clear objective, the output of the institution will not be by what society needs. secondly, methods are very important because methods are a tool to achieve a goal, thirdly, material is very important in Islamic education because it is a guide in all things, while material that must be used in Islamic education is material that leads to the practice of Islamic teachings and morals, fourthly educators, educators are individuals who will meet the knowledge, attitudes and behavior needs of students, five students. Etymologically, students in other terms are called students meaning